PROFIL USAHATANI DI DESA KAMBATATANA KECAMATAN PANDAWAI KABUPATEN SUMBA TIMUR - Sifra Varah Veronika Lena (Yayasan Akrab Pekanbaru, 2018)
The purpose of this study is to get a picture of the farming and the factors that encourage the community to conduct farming. This research uses desciptive qualitative approach. The results show (1) most farmers (54,3% of the respondents) are of 40-49 years old with a low educational background (45,7% did not graduate from the primary school); (2) land area worked by the farmers are 76 – 100 acres and 42.9% respondents work on their own land; and (3) the factor that affect the farmers to work is their own motivation. Keywords: Profile, Farming